The Public Regime for Migrant Child Education in Thailand: Alternative Depictions of Policy - Nongyao Nawarat (2018)
© 2018 Policy Studies Organization This article analyzes the conceptualization and depiction of Thailand’s public policy on education for the children of migrant workers in the country by examining a cluster of fairly recent literature on the subject. The studied texts broadly share the view that Thailand’s policy of providing full education to these children is subject to gaps and patchy implementation. An analytical review of the literature on conceptualizing this policy shows, however, that this picture is misleading as it tends to reduce policy to an idealized intention. Rather, Thailand has a plurality of local policies ambiguously governed by a national policy, which in turn does not predominantly aim at education for all. We contend that our improved characterization of the situation helps create more productive openings for research and policy change on this important topic.